Perilaku Konsumtif di Kalangan Mahasiswa Muslim Dilihat dari Penggunaan Shopeepay - Aini, Hizra; Permatasari, Najwa Pitriani; Al-Azha, Nafisah; Hidayat, Wahyu; Ibrahim, Zaini (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2024)
This research is entitled Consumptive Behavior Among Muslim Students Seen from the Use of ShopeePay. Consumptive Behavior Among Muslim Students Seen from Using ShopeePay is the name of the research. The aim of this research is to determine the consumption patterns of Muslim students and the extent to which the use of ShopeePay has an impact on these patterns. Associative and quantitative research methods were used in this research. This research uses primary data for its analysis. The primary data for this research comes directly from the research object through a questionnaire given to Muslim students class 2022 and 2024, Faculty of Islamic Economics and Business, UIN Sultan Hasanuddin Banten. The total sample was 75 respondents.